2023
DOI: 10.3390/met13081499
|View full text |Cite
|
Sign up to set email alerts
|

Particle Stimulated Nucleation Effect for Al-Mg-Zr-Sc Alloys with Ni Addition during Multidirectional Forging

Mikhail S. Kishchik,
Andrey G. Mochugovskiy,
Maxence Cuda
et al.

Abstract: The study aims to investigate the influence of fraction of coarse undeformed particles on the microstructure evolution and mechanical properties of alloys processed by isothermal multidirectional forging (MDF). For this purpose, Al-Mg-Ni-Sc-Zr-based alloys with different Ni concentrations and a fraction of Al3Ni particles of solidification origin phase were subjected to MDF at 350 °C. Precipitates of the L12-structured Al3(Sc,Zr) phase retained their structure, morphology, and size after MDF and were coherent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 89 publications
0
1
0
Order By: Relevance
“…The increase in cumulative strain and MDF temperature resulted in an increase in particle distribution homogeneity. The homogeneously distributed microscale particles can contribute to grain refinement during thermomechanical treatment and improve deformation behavior due to the particles' stimulated nucleation effect (PSN) [46,51,[63][64][65]. During MDF, the Mg 2 Si phase was noticeably fragmentized, the result of both the temperature and strain effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in cumulative strain and MDF temperature resulted in an increase in particle distribution homogeneity. The homogeneously distributed microscale particles can contribute to grain refinement during thermomechanical treatment and improve deformation behavior due to the particles' stimulated nucleation effect (PSN) [46,51,[63][64][65]. During MDF, the Mg 2 Si phase was noticeably fragmentized, the result of both the temperature and strain effect.…”
Section: Discussionmentioning
confidence: 99%
“…The MDF was performed at 150, 250, and 350 • C. The true stress vs. true strain dependencies were corrected considering the increase in the strain rate during compression [51] (Figure 3). Relatively stable flow stage occurred in a strain interval of 0.1-0.4.…”
Section: Deformation Behavior During Mdfmentioning
confidence: 99%
“…The nano-sized precipitates effectively pinned the dislocation motion and migration of the sub-grains and grain boundaries [28,36,41]. On the other hand, micronsized intermetallic particles serve as effective centers for nucleation of recrystallized grains, relying on the particle stimulated nucleation effect [41,[55][56][57][58][59][60]. These processes take place in the investigated alloys.…”
Section: Recovery and Recrystallization Behavior Of Rolled Sheetsmentioning
confidence: 97%
“…The following work also concerns with ultrafine-grained materials, specifically, an Al-Mg-Zr-Ni-based alloy. The influence of Ni addition (during multidirectional forging) on nucleation was analyzed Contribution (7). Therefore, it was concluded that nucleation and precipitate formation were favored by the addition of an element (Ni).…”
Section: Contributionsmentioning
confidence: 99%